2011
DOI: 10.1111/j.1742-9544.2010.00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Percentile Norms and Accompanying Interval Estimates from an Australian General Adult Population Sample for Self‐Report Mood Scales (BAI, BDI, CRSD, CES‐D, DASS, DASS‐21, STAI‐X, STAI‐Y, SRDS, and SRAS)

Abstract: Despite their widespread use, many self-report mood scales have very limited normative data. To rectify this, Crawford et al. have recently provided percentile norms for a series of self-report scales. The present study aimed to extend the work of Crawford et al. by providing percentile norms for additional mood scales based on samples drawn from the general Australian adult population. Participants completed a series of self-report mood scales. The resultant normative data were incorporated into a computer pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
284
19
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(334 citation statements)
references
References 39 publications
28
284
19
3
Order By: Relevance
“…For example, the levels of depression, anxiety and stress in our population were almost double the levels found in an Australian population of 18 to 24 year olds (Crawford et al 2011). Our findings, therefore, correspond with other studies in international and Saudi literature that found medical students had higher levels of psychological distress than their peers (Dahlin et al 2005;Dyrbye, et al 2006;Al-Dabal et al 2010).…”
Section: Discussionsupporting
confidence: 81%
“…For example, the levels of depression, anxiety and stress in our population were almost double the levels found in an Australian population of 18 to 24 year olds (Crawford et al 2011). Our findings, therefore, correspond with other studies in international and Saudi literature that found medical students had higher levels of psychological distress than their peers (Dahlin et al 2005;Dyrbye, et al 2006;Al-Dabal et al 2010).…”
Section: Discussionsupporting
confidence: 81%
“…It is a highly reliable measure that shows high convergent validity and has good internal consistency with a Cronbach alpha of 0.82-0.93 [34,39] Ronk et al 2013). DASS-21 sub-scale severity ratings are calculated based on the full DASS-42 severity rating [40].…”
Section: Dass-21mentioning
confidence: 99%
“…20 Depression, anxiety, and stress scores potentially warranting clinical intervention were reported by 26, 27, and 32% of the sample, respectively. In terms of posttraumatic stress symptoms, 49 participants (43%) indicated that they were "extremely" or "quite a bit" affected by one or more symptoms in the past week.…”
Section: Response Ratesmentioning
confidence: 99%
“…Depression, anxiety, and stress (21 items): The Depression, Anxiety and Stress Scale (DASS-21) is a widely used and validated measure of depression, anxiety, and stress experienced in the past 7 days, for which normative data in nonclinical Australian adult samples are available. 20 Response options range from 0 ("did not apply to me at all") to 3 ("applied to me very much or most of the time"), and clinical cutoff scores are available for each of the three subscales. 21 In the present sample, the internal consistency was 0.87 for each of the depression, anxiety, and stress subscales.…”
Section: Previously Accessed or Received Information About Geneticsmentioning
confidence: 99%